Influence of Crystallization Behavior of Gas Quenching Blast Furnace Slag on the Preparation of Amorphous Slag Beads - Yue Kang; Chao Liu; Yuzhu Zhang; Hongwei Xing (Crystals, 2020)
Slag beads with different crystal content could be obtained through the gas quenching blast furnace slag (BFS) process. In order to increase the additional value of the slag beads as much as possible, it was necessary to restrain the crystallization of the slag beads as much as possible. In this paper, the mineral types and crystallization temperatures of BFS with different basicities and cooling rates were studied by using Factsage thermodynamic software, XRD, and differential scanning calorimeter (DSC) experiments, which obtained the gas quenching temperature and the cooling rate needed to restrain crystallization behavior in the gas quenching process; The crystallization mechanism was studied by calculating crystallization activation energy (Ec) using the DSC experiment, at the same time, the thermodynamic results were verified. The proper basicity and cooling rate of BFS were found to be conducive to the preparation of amorphous slag beads. The results showed that the initial crystallization temperature decreased with decreasing the basicity and increasing the cooling rate, which could increase the amorphous content of slag beads in the gas quenching process. The crystallization activation energy (Ec) increased with decreasing basicity, which increased the crystallization barrier.